Land use differentially affects fungal communities and network complexity in northeast China - Xu, Yanxia; Yang, Zhao; Wang, Xiaolong; Chai, Hua; Li, Shasha; Wu, Yue; Wang, Ruoding (Frontiers in Microbiology, 2022)
Rhizosphere fungal communities are the one of the most important drivers of soil nutrient cycling that sustain plant growth. However, few research have been reported on the effects of different land uses on soil fungal microbial communities in the Northeast China. In this research, we use a field experiment to study the meadow, maize, and alfalfa continues cropping with different years on fungal communities and their co-occurrence networks. We showed that soil physicochemical properties such as NO3-, available phosphorus and soil pH were the most important driving factors affecting the soil fungal communities structure in different cropping systems. In addition, alfalfa succession increased some special beneficial or pathogenic fungal species, such as Mortierella and Gaiellales, compared to the cultivation of grass and maize. Compared to the cultivation of grass and maize, afalfa continues cropping increased some special beneficial or pathogenic fungal species, such as Mortierella and Gaiellales. In addition, the networks differed among plant species and also among different continues years of alfalfa cultivation, which suggests that that alfalfa continuous cropping resulting in more cooperation among fungi, which may be beneficial to the soil as well as to the development of alfalfa.